Zur ökologischen Bildersprache bei den alttestamentlichen Propheten - Najda, Andrzej (Studia Ecologiae et Bioethicae, 2006)
The prophets of the Old Testament in the fulfillment of their task of proclaiming God’s word make use of various literary forms and frequently use pictures from different disciplines of life, in order to be understandable for their listeners, in order to convince them and to make impression on them, they especially willingly make use of pictures taken from the sphere of ecology, making different comparisons and metaphors, these generally concern God, His action towards Israel and the Chosen Nation itself.